New TB treatments hiding in plain sight - Andrew J Olive; Christopher M Sassetti (EMBO Molecular Medicine)
Abstract As tuberculosis (TB) toll is revised upward according to the WHO's last estimates, the lack of vaccine strategy and the lengthy antibiotic treatments that unfortunately promote the emergence of drug resistance are a major set back in the fight against this pathogen. In this issue of EMBO Molecular Medicine, Schiebler et al (2015) propose a novel and compelling new approach to target Mycobacterium tuberculosis (Mtb) by pharmacologically stimulating intracellular mycobacteria clearance through autophagy.